Multitracer Positron Emission Tomographic Imaging of Exogenous Gene Expression Mediated by a Universal Herpes Simplex Virus 1 Amplicon Vector - Christiane Kummer; Alexandra Winkeler; Claus Dittmar; Bernd Bauer; Maria Adele Rueger; Benedikt Rueckriem; Michael T. Heneka; Stefan Vollmar; Klaus Wienhard; Cornel Fraefel; Wolf-Dieter Heiss; Andreas H. Jacobs (Molecular Imaging)
To develop efficient and safe gene therapy approaches, the herpes simplex virus type 1 thymidine kinase gene (HSV-1- tk ) has been shown to function as a marker gene for the direct noninvasive in vivo localization of thymidine kinase (TK) expression by positron emission tomography (PET) using radiolabeled nucleoside analogues as specific TK substrates. Moreover, the gene encoding dopamine type 2 receptor ( d2r ) could be used as a PET marker gene using specific radiolabeled receptor binding compounds. Here we describe the quantitative colocalization of d2r and HSV-1- tk gene expression mediated from a universal HSV-1 amplicon vector in a subcutaneous human Gli36dEGFR glioma model by PET. The HSV-1 amplicon vector was constructed using a bicistronic gene cassette to contain (1) the d2r80A mutant, which is able to bind its ligand racloprid but unable to activate downstream signal transduction pathways, and (2) the tk39 mutant with enhanced enzymatic activity toward guanosine analogues fused to the green fluorescent protein gene ( tk39gfp ) serving as a marker gene in cell culture. After infection of human Gli36dEGFR glioma cells with the HSV- d2r80A IRES tk39gfp (HSV-DITG) amplicon vector in cell culture, D2 receptor expression and its targeting to the cell surface were determined by Western blotting and immunolabeling. Vector application in vivo served for quantitative colocalization of d2r80A - and tk39gfp -derived PET signals employing the specific D2 receptor binding compound [ 11 C]racloprid and the specific TK39 substrate 9-(4-[ 18 F]fluoro-3-hydroxymethylbutyl)guanine. Our results demonstrate that for the range of gene expression studied in vivo, both enzymatic and receptor binding assays give comparable quantitative information on the level of vector-mediated gene expression in vivo. The d2r80A in combination with a specific binding compound passing the intact blood-brain barrier might be an alternative marker gene for the noninvasive assessment of vector-mediated gene expression in the brain using PET.